English pronunciation in use advanced - Hewings, Martin (United Kingdom Cambridge University Press, 2007)
This book with over four hours of free downloadable audio, includes 60 units of explanations, examples, practice exercises and answers for advanced level (C1-C2) learners of English.
Keywords: Cơ bản